Matrilineal Tradition in the Framework of Contemporary Islamic Family Law: An Analysis of Same-Clan Marriage Prohibition in West Sumatra - Krismono, Krismono; Lutfi, Muhammad; Karimuddin (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose – This study examines the prohibition of same-clan marriages in the Minangkabau community in Nagari Balun Pakan Rabaa Tengah, West Sumatra, through the lens of Islamic legal sociology. This study explores the cultural rationale behind this prohibition, highlighting its role in preserving the matrilineal structure of Minangkabau society. Despite the absence of explicit legal boundaries in Indonesian law and Islamic law, this study analyzes their alignment with Islamic legal principles in the context of contemporary Islamic family law, such as maqāṣid sharī'ah and 'urf, and their impact on social cohesion and identity.Design/methods/approach – A qualitative field research approach was adopted, involving interviews and documentation with local community members. This analysis draws on Talcott Parsons' structural functional theory (AGIL framework) and Islamic legal principles to understand the interplay between local customs and religious norms.Findings – This prohibition optimizes the functional aspects of the Minangkabau matrilineal order and promotes social adaptation, integration and goal achievement. Using the frame of contemporary Islamic family law studies, the prohibition is in line with maqāṣid sharī'ah by ensuring lineage integrity and social harmony through customary norms ('urf). The findings emphasize the ban's dual role in maintaining cultural identity and religious values.Research implications/limitations – The study's limitation lies in its focus on a single Nagari, which restricts its generalizability. Future research could extend to comparative studies across other Minangkabau regions to assess cultural variations and their implications for social structures.Originality/value – This study bridges sociology and Islamic legal studies, offering new insights into how local customs can complement religious frameworks to address societal challenges in a pluralistic context.